Management of mild Cervical Spondylotic Myelopathy - Sharma, Krishna (Nepal Journal of Neuroscience, 2024)
Introduction: Most of the elderly individuals with cervical spondylotic myelopathy (CSM) suffer from a progressive, and irreversible spinal cord dysfunction and pain. The incidence is rising in tandem with the ageing population. Due to its debilitating effects on a person's physical, mental, and social aspects, it is quickly becoming a public health issue. Therefore, the primary objective is to diagnose the condition in its milder form, prevent its progression, and treat the symptoms aggressively. This article discusses the management of mild CSM, including our experiences, difficulties, current state of knowledge, and potential future developments.Methodology: From the patients presenting with neck pain in the OPD, those with mild CSM according to modified Japanese Orthopedic Association (mJOA) scoring system were selected. Their disabilities were studies with commonly used scoring systems like Nurick grading, Neck Disability Index (NDI), and quality of life with SF-36v2. Only the degenerative cases were included, and other pathologies were excluded. Classical cervical disc prolapse with radiculopathy was also not included. Conservative management was initiated in all these patients and followed up for the improvement or deterioration.Results: With the above selection criteria, 235 patients with mild CSM were included in the studies. There were 186 males and 49 females with ages ranging from 42 to 78 years. The clinical profiles were studied. The major signs and symptoms were neck pain, disturbed dexterity of hands, imbalance on walking and exaggerated reflexes. The impairments were stratified and found that the average mJOA score was 16.2, Nurick score was 2.8 and NDI was 33.6. The quality of life was judged using SF-36v2 and was 39.7. The patients were monitored for three, six, twelve, and twenty-four months with conservative care. The follow up was very poor and only 46 out of the total 235 patients could be followed up to two years. Thus the result obtained could not derive any significant information. The symptoms like pain significantly reduced and there was improvement in overall scores including the quality of life. There were no case of deterioration during the conservative treatment. Thus, there was no discernible advancement that called for surgery.Conclusion: Mild CSM is a common, under diagnosed and usually ignored entity which affects big portion of elderly population. It specifically impacts the mental and social aspects that impairs one's quality of life, as well as the functional and emotional aspects. They are initially being treated conservatively and closely monitored for signs of worsening and advancement. Most of the patients respond to conservative treatment but those having risk factors for progression and bad prognosis, should remain vigilant of any features of deterioration. The treatment plan must be timely modified if a patient's clinical condition deteriorates preventing life-long sufferings.